1993
DOI: 10.1021/j100151a053
|View full text |Cite
|
Sign up to set email alerts
|

FT-IR study of polymorphic transformations in SOS, POP, and POS

Abstract: Study of molecular structures with Fourier transform ( I T ) infrared (IR) spectroscopy has been done on polymorphic transformations of three saturated-unsaturated mixed acid triacylglycerols (TAGs): sn-1,3-stearoyl-2-oleoyl glycerol (SOS), sn-1,3-palmitoyl-2-oleoyl glycerol (POP), and sn-1,3-palmitoylstearoyl-2-oleoyl glycerol (POS), in combination with X-ray diffraction and differential scanning calorimetry (DSC). Specific attention has been paid to absorption bands corresponding to methyl end packing, olefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 12 publications
(19 reference statements)
8
53
1
Order By: Relevance
“…This suggests that conformational differences exist between the polymorphs of SHs and Si‐SHs around the carbonyl bond, which is resolvable in Raman spectra. Similar observations were reported in the case of cocoa butter TAGs , StOSt (by conventional IR) and tristearin . However, Sprunt et al reported two bands for the β form of StOSt TAG.…”
Section: Resultssupporting
confidence: 78%
“…This suggests that conformational differences exist between the polymorphs of SHs and Si‐SHs around the carbonyl bond, which is resolvable in Raman spectra. Similar observations were reported in the case of cocoa butter TAGs , StOSt (by conventional IR) and tristearin . However, Sprunt et al reported two bands for the β form of StOSt TAG.…”
Section: Resultssupporting
confidence: 78%
“…This indicates that the increase in the SLS concentration may have prohibited the occurrence of the β′ form in the SOS/SLS mixture during α-melt mediation. Figure 5 shows results of the RA-XRD study of the α-melt-mediated transformation of SOS, SOS/SLS mixtures (75:25 and 70: 30), and SLS when the α form was rapidly heated from 10 to 36°C. In the 75:25 SOS/SLS mixture, the β 2 form of the SOS fraction crystallized immediately, and the SLS fraction melted together with a small amount of the SOS fraction.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to understand the physical properties of the binary mixture phases of SOS and SLS, since this mixing behavior is closely related to fat blending in fat technology and the separation of fats and oils in industrial crystallization processes. The thermal and structural properties of SOS (29)(30)(31) and SLS (32) are summarized in Table 1. SOS has five polymorphic forms-α, γ, β′, and two β forms-and SLS has two forms-α and γ.…”
mentioning
confidence: 99%
“…Figure 16 clearly indicates that the thermal factors are becoming higher 7) 114.4 (6) 114.2(6) C(6)-C(7)-C (8) 113.0(6) 113.8(6) C(7)-C(8)-C (9) 113.5 (6) 113.3(6) C(8)-C(9)-C (10) 114.0(6) 113.7(6) C(9)-C(10)-C (11) 113.6(6) 113.0(6) C(10)-C(11)-C (12) 114.4 (7) 112.9(7) C(11)-C(12)-C (13) 113.2 (7) 113.0(8) C(12)-C(13)-C (14) 127 179 (4) 176 (4) starting from the 15th carbon atom toward the methyl terminal. Specially large thermal factors around the methyl terminal may reflect the conformational disorders observed in Raman spectroscopy.…”
Section: Changes In Chainmentioning
confidence: 97%
“…In the field of glycerides, it has been also clarified that polymorphism of glycerides becomes more complex by introduction of cis-unsaturated chains. [6][7][8] However, detailed structures of cis-unsaturated acyl chains in these systems are still unclear.…”
Section: Introductionmentioning
confidence: 99%